Bio-pesticide properties of vermicompost. - Domínguez, Jorge; Gómez-Brandón, María; Lazcano, Cristina (Instituto de Ecología, A.C., 2010)
Despite the extensive literature on the suppression of pests by some organic fertilizers like compost, there are very few studies related to the control of pests by vermicompost. Recently, the potential of vermicompost in the suppression of plant pathogens, insects, mites and plant parasitic nematodes has been investigated. The addition of vermicompost to soils increases microbial diversity, providing a wider range of microorganisms that can act as biocontrol agents against different plant plagues. Furthermore, vermicompost is a slow releasing nutrient source providing nutrients in synchrony with plant needs, and its application can increase the production of phenolic compounds in plants, making them more resistant to herbivory. Although, there is scientific evidence of the role of vermicompost in the suppression of pests, it is necessary to clarify which factors trigger this suppression and to what extent these are dependent on the source of the material, on the species of earthworm and the vermicomposting process.